Association Between Age and Patient‐Reported Changes in Voice and Swallowing After Thyroidectomy. (7th September 2018) - Sahli, Zeyad; Canner, Joseph K.; Najjar, Omar; Schneider, Eric B.; Prescott, Jason D.; Russell, Jonathon O.; Tufano, Ralph P.; Zeiger, Martha A.; Mathur, Aarti
Abstract : Objectives: Despite intact recurrent laryngeal nerves, patient‐reported voice and swallowing changes are common after thyroidectomy. The association between patient age or frailty status and these changes is unknown. The aim of this study was to evaluate the impact of age and frailty on the incidence of voice and swallowing alterations after thyroidectomy. Methods: We performed an institutional review board (IRB)‐approved retrospective review of consecutive patients who underwent total thyroidectomy with intraoperative recurrent laryngeal nerve (RLN) monitoring at a single institution between January 2014 and September 2016. Patients with RLN injury were excluded. After data extraction, a modified frailty index (mFI) was calculated for each patient. The association among risk factors, including age, mFI, prior history of neck surgery, frequent voice use, presence of malignancy or gastroesophageal reflux disease, and smoking status and reported voice and/or swallowing changes was examined. Results: Of 924 patients undergoing thyroidectomy, 148 (16.0%) reported only changes in voice; 52 (5.6%) reported only difficulty in swallowing; and 26 (2.8%) reported changes with both voice and swallowing. On multivariate analysis, we found a significant increase in voice or swallowing alterations up to the age of 50 years (5% increased odds per year), after which these changes plateaued. We found that mFI was not associated with voice or swallowing changes. Conclusion: Age ≥ 50 years is independently associated with the development of voice or swallowing changes after thyroidectomy, despite intact RLN. Additional prospective studies are needed to validate these findings, further define this association, and identify risk factors for developing these changes. Level of Evidence: 2b Laryngoscope, 129:519–524, 2019